Psychological Aspects of Agingp - Mooney, Craig M. (Canadian Journal of Counselling and Psychotherapy, 2012)
Psychological aspects of aging, based on gerontological hypotheses and research findings, are presented under three headings; intellectual abilities; emotional capacities; motor capabilities. Consequent practical implications of such facts and ideas for persons concerned with the well-being of aged persons are discussed.